KONDISI PLANKTON PADA TAMBAK UDANG WINDU (Penaeus monodon FABRICIUS) DENGAN SUBSTRAT BERBEDA - Erfan Andi Hendrajat; Andi Sahrijanna (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Plankton is one of water microorganisms that plays an important role as natural food for fish and shrimp and as an stability indicator of water or aquatic environment.The purpose of this study was to determine the composition and abundance of plankton in tiger shrimp ponds using concrete ponds without substrate, concrete ponds using sand substrate and ponds. Sampling of plankton and water quality was carried out from March to July 2016 at PunagaTakalar Experimental Pond at 6 ponds consisted of concrete ponds without 2 subplot of sand (pond A) and concrete pond with 2 subplate sand subplate (pond B) respectively measuring 1,000 m2 and a 2-square-meter plot of 2,500–3,000 m2 (pond C). The results showed that plankton abundance in pond A ranged from 37–349 individuals/L, pond B ranged from 35–1,399 individuals/L and pond C ranged from 54–999 individuals/L. The most common phytoplankton genera in this study was Oscillatoria while for zooplankton is of Acartia. The diversity of plankton in ponds A, B and C is included in the community of unstable to moderate biota. In general, the diversity of plankton in pond B is included in the community of moderate biota. The plankton uniformity index in pond A, pond B and pond C is generally close to 1 this indicates that the existence of plankton species in the three ponds is relatively even.